Good clinical practice for investigators conducting clinical trials - Tivadar, Andrijana (Anali PAZU, 2023)
Drug development is a long and expensive process. Before a particular drug receives the appropriate marketing authorization, it is necessary to prove its efficacy and safety in addition to its quality. Clinical trials are necessary to prove the effectiveness and safety of the drug. A clinical trial of a drug is research conducted on healthy individuals and patients, in which the principles of good clinical practice (GCP) must be followed. Compliance with this standard provides public assurance that the rights, safety and wellbeing of trial subjects are protected and that clinical-trial data are credible. A clinical trial of a drug involves investigators, sponsors, and participants. In this paper, we focus on the investigator in the clinical trial of a drug, who must be well aware of the principles of GCP in order to be able to comply with his obligations and responsibilities. By showing examples of deficiencies identified during clinical trial site inspection (at the investigator), we aim to help investigators to achieve compliance with good clinical practice.